Worker Participation and Industrial Relations – The Trend Toward Decentralization - Wertheim, Edward (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The author examines the recent developments in worker participation in the context of overall patterns in industrial relations. In Europe, it appears as a complement to traditional patterns, an attempt to decentralize influence. Efforts toward worker control are likely to have limited appeal in places such as the United States and Britain where labour perceives industrial relations as already fairly decentralized.